Letters of the great kings of the ancient Near East : the royal correspondence of the late Bronze Age - Bryce, Trevor, 1940- (Routledge : Taylor & Francis, 2003)
From the 17th to the 12th centuries BCE, the five Great Kings of Egypt, Babylon, Hatti (the kingdom of the Hittites), Mitanni and Assyria ruled over vast, complex territories. One of the secrets to their control was frequent communication by letter.